Frailty Questionnaire Is Not a Strong Prognostic Factor for Functional Outcomes in Hip or Knee Arthroplasty Patients. (25th January 2019) - Meessen, Jennifer M. T. A.; Fiocco, Marta; Leichtenberg, Claudia S.; Vliet Vlieland, Thea P. M.; Slagboom, P. Eline; Nelissen, Rob G. H. H.
Introduction: Up to 33% and 25% of patients with end-stage hip and knee osteoarthritis (OA) are considered frail by the Groningen Frailty Indicator (GFI). This study aims to assess whether frail patients have lower functional gains after arthroplasty and to assess GFI as a tool to discriminate between good and adverse change score. Materials and Methods: Patients with end-stage hip/knee OA scheduled for arthroplasty were recruited from the Longitudinal Leiden Orthopaedics Outcomes of Osteo-Arthritis Study . Functional outcome was measured as change score on the Hip Osteoarthritis Outcome Score/Knee Osteoarthritis Outcome Score (HOOS/KOOS), by subtracting preoperative score from 1-year postsurgery score and then dichotomized based on a cutoff of 20 points. For each HOOS/KOOS subscale, 3 models were estimated: GFI univariate (model 1), GFI and baseline score (model 2), and baseline score univariate (model 3). A receiver operating characteristic analysis was performed to assess the discriminative ability of each model. Results: Eight hundred five patients with end-stage hip OA (31.4% frail) and 640 patients with end-stage knee OA (25.4% frail) were included. Frail patients were older, had a higher body mass index, had more comorbidities, and lived more often alone. Persons considered frail by GFI had significant lower baseline score; however, except for "function in sports and recreation" and "quality of life, " change scores were similar in frail and nonfrail persons. The discriminatory value of GFI was negligible for all HOOS/KOOS subscales. Baseline score, however, was adequate to discriminate between total knee arthroplasty patients with more or less than twice the minimally clinically important difference on KOOS symptoms subscale (area under the curve = 0.802). Discussion/Conclusion: Although frail patients with OA have lower functioning scores at baseline, the change scores on HOOS/KOOS subscales are similar for both frail and nonfrail patients. Exploring other heath assessements may improve patient-specific outcome prediction.